'We're Not a White Fella Organization': Hybridity and friction in the contact zone between local kinship relations and audit culture in an Indigenous organization. Issue 5 (May 2023) - Cutcher, Leanne; Dale, Karen
Our paper contributes to studies of Indigenous organizing and organizations. We draw on Indigenous knowledge which recognizes that everything is connected within networks of relationships to extend post-colonial theory on hybridity. Our case study research with Australia's only Indigenous-owned credit union identifies how hybridity is co-constituted through 'friction' in the 'contact zone' where local kinship relations and audit practices meet and grapple. Focusing on the 'contact zone' allows us to better understand the everyday organizing that produces hybridity. We build on existing work on hybridities in organizations which predominately focus on issues of language and knowledge by focusing on the organizational interactions themselves, especially the embedded interactions between humans and objects. Seeing these interactions as 'friction' means not trying to solve or dissolve them – but to acknowledge them as lived realities of an Indigenous organization.